Metallurgical solid waste gel material and preparation method thereof

By using specific ratios of slag ultrafine powder, construction gypsum powder, stainless steel slag powder, fly ash and coking desulfurization ash in metallurgical solid waste gelling materials, the problem of not adapting to different application scenarios is solved, and the early strength improvement of the material and the satisfaction of environmental protection standards are achieved.

CN119707329APending Publication Date: 2025-03-28BAOWU HUANKE SHANXI RESOURCE RECYCLING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411890654.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing metallurgical solid waste gelling materials have problems in the setting time of inadequate to different application scenarios, and the utilization rate of steel slag and stainless steel slag is low, and there is a risk of stability and heavy metal dissolution exceeding the standard.

Method used

The ratio of 40-60% slag ultrafine powder, 5-15% construction gypsum powder, 5-20% stainless steel slag powder, 5-10% fly ash and 1-8% coking desulfurization ash is adjusted through ball milling and screening treatment.

Benefits of technology

The early compressive strength and flexural strength of gelled materials have been improved, which meets the construction time requirements of different scenarios, reduces the content of water-soluble hexavalent chromium, meets environmental protection standards, and improves the utilization rate of solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a metallurgical solid waste gel material which comprises the following components in percentage by mass: 40-60% of superfine slag powder, 5-15% of building gypsum powder, 5-20% of stainless steel slag powder, 5-10% of fly ash and 1-8% of coking desulfurization ash, the superfine slag powder is prepared by conveying blast furnace water-quenched slag generated by ironmaking into a storage tank through a belt and then grinding the blast furnace water-quenched slag into a vertical mill; according to the invention, sodium sulfate of coking desulfurization ash is utilized to excite condensation and hardening of superfine slag powder, and development of compressive strength is promoted. Sodium sulfate can react with calcium in the stainless steel slag powder in the early stage to generate gypsum and sodium hydroxide, sufficient gypsum is provided for reacting with tricalcium aluminate, a large amount of ettringite is generated in the early stage, and the bonding strength is enhanced; compared with the common method using desulfurized gypsum, the addition of the building gypsum powder can adjust the setting time of the cementing material, and can flexibly, conveniently and quickly adjust the application in different scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of comprehensive resource utilization, and in particular to a metallurgical solid waste gel material and a preparation method thereof. Background Art

[0002] The steel industry covers a wide range and has many processes, so it produces a lot of solid waste, including blast furnace slag, metallurgical steel slag, various metallurgical dust and mud, and desulfurization products from supporting power plants and coking plants. Among them, steel slag, which has the highest production volume, contains free calcium and magnesium oxide, which poses a risk of stability in use, and its utilization rate is lower than that of other solid wastes; the presence of heavy metal chromium in stainless steel slag in steel slag poses a risk of radioactivity and excessive heavy metal dissolution in the application field, and its utilization rate is even lower. Coking desulfurization ash is a product of coking desulfurization, and its main component is sodium sulfate, which is difficult to handle. Using metallurgical solid waste from steel mills to prepare low-carbon, green, clinker-free cementitious materials is one of the best solutions for the coordinated utilization of solid wastes, and it is also the best way to achieve the resource utilization of solid wastes, and it is a great contribution to the realization of the "dual carbon" goals.

[0003] Traditional cementitious materials made from mineral powder, steel slag, and industrial by-product gypsum have a slow setting time. The setting time cannot be adjusted due to different customer requirements for different application scenarios such as concrete mixing plants and dry-mix mortar. Summary of the invention

[0004] The object of the present invention is to provide a metallurgical solid waste gel material and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a metallurgical solid waste gel material, which comprises, by mass percentage, 40-60% of ultrafine slag powder, 5-15% of building gypsum powder, 5-20% of stainless steel slag powder, 5-10% of fly ash and 1-8% of coking desulfurization ash.

[0006] Preferably, the ultrafine slag powder is obtained by conveying water-quenched blast furnace slag produced by iron smelting into a storage tank via a belt, and then grinding it into a vertical mill.

[0007] Preferably, the building gypsum powder is prepared by conveying the gypsum slurry produced by the desulfurization tower of the power plant through a vacuum belt into a double-axis screw device, and then entering the rotary kiln through the double-axis screw, controlling the temperature at the kiln tail at 140-180°C, the crystal water content at 6-7%, and then undergoing ball milling modification. The obtained slag ultrafine powder is placed in a storage tank for standby use.

[0008] Preferably, the stainless steel slag powder is obtained by grinding stainless steel slag in a ball mill after wet metal selection.

[0009] Preferably, the blast furnace water-quenched slag is ground in a vertical mill to obtain an ultrafine slag powder having a specific gravity of 300-420 cm2 / kg and a moisture content of 0.01-0.99.

[0010] Preferably, the specific gravity of the stainless steel slag powder obtained by ball milling in the ball mill is 600-700 cm2 / kg.

[0011] A method for preparing a metallurgical solid waste gel material according to any one of the above, comprising the following steps:

[0012] S1. Place ultrafine slag powder, building gypsum powder, stainless steel slag powder, fly ash, and coking desulfurization ash into separate storage tanks;

[0013] S2, weighing the material through a spiral weighing scale, and conveying the weighed material into a ball mill through a screw conveyor for ball milling;

[0014] S3, the ball milled material is passed through a 0.045 square hole sieve, and the material fineness is controlled at 5-10% of the sieve residue;

[0015] S4. After the materials are mixed to meet the fineness requirements, they are transported by the elevator into the storage tank. The materials are then sent to the packaging equipment via the screw conveyor system for bagging and sales.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. The present invention produces a cementitious material with a 3-day compressive strength of 18 MPa, a flexural strength of 4.5 MPa, a 28-day compressive strength of 43.5 MPa, a flexural strength of 8.5 MPa, and a water-soluble hexavalent chromium of 0.9 mg / kg, through the synergistic stimulation between solid wastes, which meets the requirements of the 425 index of silicate cement.

[0018] 2. The solid waste cementitious material of the present invention utilizes sodium sulfate in coking desulfurization ash to stimulate the coagulation and hardening of ultrafine slag powder and promote the development of compressive strength. Sodium sulfate can react with calcium in stainless steel slag powder at an early stage to generate gypsum and sodium hydroxide, providing sufficient gypsum to react with tricalcium aluminate, generating a large amount of calcium vanadium at an early stage, and enhancing the cementitious strength.

[0019] 3. The addition of building gypsum powder of the present invention can adjust the setting time of the cementitious material compared with the general method of using desulfurized gypsum, and can make flexible, convenient and rapid adjustments for applications in different scenarios.

[0020] 4. The present invention uses all solid waste, can realize comprehensive utilization of waste residues, turn waste into treasure, create economic value, and protect the environment, which is of great significance.

[0021] 5. The present invention can adjust the mixing ratio of building gypsum powder and coking desulfurization ash according to the customer's setting time requirements, ensuring the strength while quickly, conveniently and cost-effectively regulating the construction time. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] The present invention provides a technical solution: a metallurgical solid waste gel material, which comprises, by mass percentage, 40-60% of ultrafine slag powder, 5-15% of building gypsum powder, 5-20% of stainless steel slag powder, 5-10% of fly ash and 1-8% of coking desulfurization ash.

[0024] Ultrafine slag powder is produced by using blast furnace water-quenched slag produced by iron smelting, which is conveyed by belt into a storage tank and then into a vertical mill for grinding.

[0025] Building gypsum powder is made by conveying the gypsum slurry produced by the desulfurization tower of the power plant through a vacuum belt into a double-axis screw device, and then into a rotary kiln via a double-axis screw. The temperature at the kiln tail is controlled at 140-180°C, and the crystal water content is between 6-7%. It is then prepared after ball milling modification. The obtained slag ultrafine powder is placed in a storage tank for standby use.

[0026] Stainless steel slag powder is made by grinding stainless steel slag into a ball mill after wet metal selection.

[0027] The blast furnace water-quenched slag is ground in a vertical mill to produce ultrafine slag powder with a specific gravity of 300-420 cm2 / kg and a moisture content of 0.01-0.99.

[0028] The specific gravity of the stainless steel slag powder obtained by ball milling in a ball mill is 600-700cm2 / kg.

[0029] A method for preparing a metallurgical solid waste gel material according to any one of the above items comprises the following steps:

[0030] S1. Place ultrafine slag powder, building gypsum powder, stainless steel slag powder, fly ash, and coking desulfurization ash into separate storage tanks;

[0031] S2, weighing the material through a spiral weighing scale, and conveying the weighed material into a ball mill through a screw conveyor for ball milling;

[0032] S3, the ball milled material is passed through a 0.045 square hole sieve, and the material fineness is controlled at 5-10% of the sieve residue;

[0033] S4. After the materials are mixed to meet the fineness requirements, they are transported by the elevator into the storage tank. The materials are then sent to the packaging equipment via the screw conveyor system for bagging and sales.

[0034] Example 1

[0035] A metallurgical solid waste gel material comprises, by mass percentage, 40% of ultrafine slag powder, 5% of building gypsum powder, 5% of stainless steel slag powder, 5% of fly ash and 1% of coking desulfurization ash.

[0036] Ultrafine slag powder is produced by using blast furnace water-quenched slag produced by iron smelting, which is conveyed by belt into a storage tank and then into a vertical mill for grinding.

[0037] Building gypsum powder is made by conveying the gypsum slurry produced by the desulfurization tower of the power plant through a vacuum belt into a double-axis screw device, and then into a rotary kiln via a double-axis screw. The temperature at the kiln tail is controlled at 140-180°C, and the crystal water content is between 6-7%. It is then prepared after ball milling modification. The obtained slag ultrafine powder is placed in a storage tank for standby use.

[0038] Stainless steel slag powder is made by grinding stainless steel slag into a ball mill after wet metal selection.

[0039] The blast furnace water-quenched slag is ground in a vertical mill to produce ultrafine slag powder with a specific gravity of 300-420cm2 / kg and a moisture content of less than 1.

[0040] The specific gravity of the stainless steel slag powder obtained by ball milling in a ball mill is 600-700cm2 / kg.

[0041] According to the above method for preparing a metallurgical solid waste gel material, the following steps are included:

[0042] S1. Put 40% of ultrafine slag powder, 5% of building gypsum powder, 5% of stainless steel slag powder, 5% of fly ash and 1% of coking desulfurization ash into separate storage tanks;

[0043] S2, weighing the materials through a spiral weighing scale, and proportioning them. The weighed materials are conveyed into a ball mill through a screw conveyor for ball milling;

[0044] S3, the ball milled material is passed through a 0.045 square hole sieve, and the material fineness is controlled at 10% of the sieve residue;

[0045] S4. After the materials are mixed to meet the fineness requirements, they are transported by the elevator into the storage tank. The materials are then sent to the packaging equipment via the screw conveyor system for bagging and sales.

[0046] Example 2

[0047] A metallurgical solid waste gel material, comprising, by mass percentage, 50% of ultrafine slag powder, 10% of building gypsum powder, 10% of stainless steel slag powder, 7.5% of fly ash and 4% of coking desulfurization ash.

[0048] According to the above method for preparing a metallurgical solid waste gel material, the following steps are included:

[0049] S1. Put 50% of slag ultrafine powder, 10% of building gypsum powder, 10% of stainless steel slag powder, 7.5% of fly ash and 4% of coking desulfurization ash into separate storage tanks;

[0050] S2, weighing the materials through a spiral weighing scale, and proportioning them. The weighed materials are conveyed into a ball mill through a screw conveyor for ball milling;

[0051] S3, the ball milled material is passed through a 0.045 square hole sieve, and the material fineness is controlled at 5% of the sieve residue;

[0052] S4. After the materials are mixed to meet the fineness requirements, they are transported by the elevator into the storage tank. The materials are then sent to the packaging equipment via the screw conveyor system for bagging and sales.

[0053] Ultrafine slag powder is produced by using blast furnace water-quenched slag produced by iron smelting, which is conveyed by belt into a storage tank and then into a vertical mill for grinding.

[0054] Building gypsum powder is made by conveying the gypsum slurry produced by the desulfurization tower of the power plant through a vacuum belt into a double-axis screw device, and then into a rotary kiln via a double-axis screw. The temperature at the kiln tail is controlled at 140-180°C, and the crystal water content is between 6-7%. It is then prepared after ball milling modification. The obtained slag ultrafine powder is placed in a storage tank for standby use.

[0055] Stainless steel slag powder is made by grinding stainless steel slag into a ball mill after wet metal selection.

[0056] The blast furnace water-quenched slag is ground in a vertical mill to produce ultrafine slag powder with a specific gravity of 300-420cm2 / kg and a moisture content of less than 1.

[0057] The specific gravity of the stainless steel slag powder obtained by ball milling in a ball mill is 600-700cm2 / kg.

[0058] Example 3

[0059] A metallurgical solid waste gel material comprises, by mass percentage, 60% of ultrafine slag powder, 15% of building gypsum powder, 20% of stainless steel slag powder, 10% of fly ash and 8% of coking desulfurization ash.

[0060] Ultrafine slag powder is produced by using blast furnace water-quenched slag produced by iron smelting, which is conveyed by belt into a storage tank and then into a vertical mill for grinding.

[0061] Building gypsum powder is made by conveying the gypsum slurry produced by the desulfurization tower of the power plant through a vacuum belt into a double-axis screw device, and then into a rotary kiln via a double-axis screw. The temperature at the kiln tail is controlled at 140-180°C, and the crystal water content is between 6-7%. It is then prepared after ball milling modification. The obtained slag ultrafine powder is placed in a storage tank for standby use.

[0062] Stainless steel slag powder is made by grinding stainless steel slag into a ball mill after wet metal selection.

[0063] The blast furnace water-quenched slag is ground in a vertical mill to produce ultrafine slag powder with a specific gravity of 300-420cm2 / kg and a moisture content of less than 1.

[0064] The specific gravity of the stainless steel slag powder obtained by ball milling in a ball mill is 600-700cm2 / kg.

[0065] According to the above method for preparing a metallurgical solid waste gel material, the following steps are included:

[0066] S1. Put 60% of ultrafine slag powder, 15% of building gypsum powder, 20% of stainless steel slag powder, 10% of fly ash and 8% of coking desulfurization ash into separate storage tanks;

[0067] S2, weighing the materials through a spiral weighing scale, and proportioning them. The weighed materials are conveyed into a ball mill through a screw conveyor for ball milling;

[0068] S3, the ball milled material is passed through a 0.045 square hole sieve, and the material fineness is controlled at 2% of the sieve residue;

[0069] S4. After the materials are mixed to meet the fineness requirements, they are transported by the elevator into the storage tank. The materials are then sent to the packaging equipment via the screw conveyor system for bagging and sales.

[0070] The proportioning scheme designs in Examples 1 to 3 are shown in Table 1:

[0071] Table 1 Proportion scheme

[0072]

[0073] Description: Ultrafine slag powder is the main component of the material, and its high specific surface area is beneficial to increase the early strength of the material; the addition of building gypsum not only helps to adjust the setting time, but also reacts with calcium ions in the slag to form calcium aluminate, further improving the strength, and adjusting its setting time through different proportions; stainless steel slag powder contains a high content of calcium, which can promote the hydration reaction of slag and further improve the strength after hardening, especially the compressive strength after 28 days; fly ash provides a certain amount of mineral admixture, which can improve the workability of the mixed material, slow down the reaction process, and improve the long-term strength; coking desulfurization ash, as an activator, contains sodium sulfate, which can promote the setting and hardening of ultrafine slag powder and improve the early strength.

[0074] Test 1: Strength test:

[0075] According to each ratio in Example 1 to Example 3, the compressive strength and flexural strength at 3 days and 28 days were tested. The test results are shown in Table 2 below:

[0076] Table 2 Compressive and flexural strength

[0077]

[0078] According to the results in Table 2, as the proportion of ultrafine slag powder increases, the compressive strength gradually increases, especially the compressive strength at 28 days; as the stainless steel slag powder and building gypsum powder increase, the flexural strength increases; in Example 3, the compressive strength value at 3 days is the largest, which is 20 MPa, and the compressive strength value at 28 days is the largest, which is 42 MPa; similarly, in Example 3, the flexural strength at 3 days is the largest, which is 6 MPa, and the flexural strength at 28 days is the largest, which is 10 MPa, so Example 3 is the best embodiment of the present invention.

[0079] Test 2: Coagulation time test:

[0080] The amount of building gypsum powder added: The increase in the proportion of building gypsum powder can adjust the setting time. When the proportion is low (such as 5%), the setting time is shorter; when the proportion is high (such as 15%), the setting time is longer.

[0081] By adjusting the proportion of gypsum powder, ensure that the setting time is neither too fast (affecting construction time) nor too slow (affecting the improvement of early strength).

[0082] Experimental steps:

[0083] 1. Raw material preparation: According to the above proportions, prepare the slag ultrafine powder, building gypsum powder, stainless steel slag powder, fly ash and coking desulfurization ash respectively and store them in separate storage tanks;

[0084] 2. Weighing and mixing: Use a screw weighing scale to accurately weigh and send each component into the ball mill through a screw conveyor for ball milling;

[0085] 3. Screening and mixing: After ball milling, screen through a 0.045 square hole sieve to ensure uniform material fineness. Control the screen residue between 5-10%;

[0086] 4. Setting time and strength determination: The performance of each mix is ​​evaluated through standard setting time tests and strength tests (such as compressive strength and flexural strength).

[0087] 5. Packaging and storage: The mixture that meets the requirements is sent to the storage tank through the elevator, and then sent to the packaging equipment for packaging through the screw conveyor system.

[0088] Through experiments, the compressive strength, flexural strength, setting time and changes in water-soluble hexavalent chromium of the material under different ratios were verified, and finally the optimal ratio was screened out.

[0089] The results are shown in Table 3:

[0090] Table 3

[0091] Ratio Setting time (hours) Water-soluble hexavalent chromium (mg / kg) Example 1 2.5 hours 0.8mg / kg Example 2 4 hours 0.7mg / kg Example 3 6 hours 0.9mg / kg

[0092] The results show that increasing the proportion of building gypsum powder (such as Example 3) will prolong the setting time, which can adjust the construction time of the material; all proportions of water-soluble hexavalent chromium in Examples 1 to 3 are within the environmental protection standard range, ensuring the safety of the material.

[0093] In summary, the hexavalent chromium content of the cementitious material prepared by the present invention is ≤10 mg / kg after testing. The strength grade can meet the 425 grade requirement in the general Portland cement standard, which is beneficial to reducing comprehensive costs and energy consumption, and has great significance for environmental protection.

[0094] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A metallurgical solid waste gel material, characterized in that: Calculated by mass percentage, the metallurgical solid waste gel material includes: 40-60% of ultrafine slag powder, 5-15% of building gypsum powder, 5-20% of stainless steel slag powder, 5-10% of fly ash and 1-8% of coking desulfurization ash.

2. The metallurgical solid waste gel material according to claim 1, characterized in that: The ultra-fine slag powder is produced by conveying blast furnace water-quenched slag produced during ironmaking into a storage tank via a belt, and then entering a vertical mill for grinding.

3. The metallurgical solid waste gel material according to claim 1, characterized in that: The building gypsum powder is prepared by using gypsum slurry produced by a desulfurization tower of a power plant, which is transported by a vacuum belt into a double-axis screw device, and then enters a rotary kiln via a double-axis screw. The temperature at the kiln tail is controlled at 140-180°C, the crystal water content is between 6-7%, and then it is ball-milled and modified. The obtained slag ultrafine powder is placed in a storage tank for standby use.

4. The metallurgical solid waste gel material according to claim 1, characterized in that: The stainless steel slag powder is obtained by grinding stainless steel slag into a ball mill after wet metal selection.

5. The metallurgical solid waste gel material according to claim 2, characterized in that: The blast furnace water-quenched slag is ground in a vertical mill to obtain an ultrafine slag powder having a specific gravity of 300-420 cm2 / kg and a moisture content of 0.01-0.

99.

6. The metallurgical solid waste gel material according to claim 4, characterized in that: The specific surface area of ​​the stainless steel slag powder obtained by ball milling in the ball mill is 600-700 cm2 / kg.

7. A method for preparing a metallurgical solid waste gel material according to any one of claims 1 to 6, characterized in that: The steps include: S1. Place ultrafine slag powder, building gypsum powder, stainless steel slag powder, fly ash, and coking desulfurization ash into separate storage tanks; S2, weighing the material through a spiral weighing scale, and conveying the weighed material into a ball mill through a screw conveyor for ball milling; S3, the ball milled material is passed through a 0.045 square hole sieve, and the material fineness is controlled at 5-10% of the sieve residue; S4. After the materials are mixed to meet the fineness requirements, they are transported by the elevator into the storage tank. The materials are then sent to the packaging equipment via the screw conveyor system for bagging and sales.